Konsep Konsolidasi Untuk Media Luar Ruang Pada PT. X - Patrick Oswin; Jani Rahardjo (Jurnal Titra, 2018)
PT. X is a company that manufactures consumer goods in Indonesia. This thesis focused on what the possibilities could happen afthe consolidation concept applied in current outdoor media system in PT. X. consolidation is a way that already applied in most of big company to minimize information activity between the company and third party or supplier(s). PT. X stiil using conventional way to handle all the outdoor media used. There’s 189 supplier that PT. X managed regularly by contacted each supplier. This method cause various problem such as longer communication chain and miscommunication. The number of supplier that PT. X use also reduced by 2015 to 2017. Reduced percentage between those years’ 39% and this affect the number of spot used by PT. X. Number of spot PT. X use also reduced by 35% from 2015 to 2017. After seeing this problem the improvement that we can proposed is consolidation process inside PT. X. Consolidation will use centralized information principle. The result from this thesis is consolidation concept that soon apply to PT. X outdoor media system.